2015
DOI: 10.1007/s13410-015-0410-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of poor sleep quality, family history of type 2 diabetes, and abdominal obesity on impaired fasting glucose: a population-based cross-sectional survey in China

Abstract: This study aims to explore the interaction of sleep quality, family history of type 2 diabetes, and obesity in relation to impaired fasting glucose in a Chinese population. A representative population-based cross-sectional study was conducted, and 15,145 residents aged between 18 and 75 years were selected from 11 districts of Xuzhou City, Jiangsu Province. The Pittsburgh Sleep Quality Index was used to evaluate sleep conditions, with categories of good and poor. Impaired fasting glucose (IFG) was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…Irrespective of the previous findings (Chou et al, 2020;Hung et al, 2013;Kim et al, 2018;Qin et al, 2016;Roddy et al, 2013), we could not demonstrate any association of the quality and duration of sleep, and the combination of both of them with IFG and hyperuricemia. Even after adjusting the predictive model using age and gender (IFG and hyperuricemia) and shift worker (only hyperuricemia), we remained failure to detect any significant association.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Irrespective of the previous findings (Chou et al, 2020;Hung et al, 2013;Kim et al, 2018;Qin et al, 2016;Roddy et al, 2013), we could not demonstrate any association of the quality and duration of sleep, and the combination of both of them with IFG and hyperuricemia. Even after adjusting the predictive model using age and gender (IFG and hyperuricemia) and shift worker (only hyperuricemia), we remained failure to detect any significant association.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, impaired fasting glucose (IFG) as including the prediabetes criteria, could rise type 2 diabetes mellitus risk (American Diabetes Association, 2020). Interestingly, several observational studies have reported that poor sleep quality could enhance prediabetes risk (Hung et al, 2013;Qin et al, 2016). Similarly, many meta-analysis studies had revealed that sleep quality and quantity assist to insulin sensitivity, glucose tolerance, and risk of diabetes (Chattu et al, 2019;Kothari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%